Alcohol Use and Problems as a Potential Mediator of the Relationship between Emotion Dysregulation and IPV Perpetration - Grigorian, Hannah L. (Psychol Violence, 2019)
OBJECTIVE: Alcohol use/problems and emotion dysregulation are associated with increased intimate partner violence (IPV) perpetration. Additionally, alcohol use is an overt coping mechanism for dysregulated emotion. While past research has examined alcohol use/problems as a mediator between emotion dysregulation and IPV, research is limited within clinical samples. The current study sought to fill this gap by examining a theoretical model by which emotion dysregulation and alcohol use/problems influence IPV perpetration in a sample of men arrested for domestic violence. Consistent with prior research, it was hypothesized that alcohol use/problems would mediate the relationship between emotion dysregulation and psychological aggression. Additionally, we hypothesized that emotion dysregulation would positively associate with increased alcohol use/problems, which would relate to increased physical assault perpetration through psychological aggression perpetration. METHOD: Using a cross-sectional sample of 391 men arrested for domestic violence and court-referred to Batterer Intervention Programs (BIP), the present study used structural equation modeling to examine proposed pathways from emotion dysregulation to IPV perpetration directly and indirectly through alcohol use/problems. RESULTS: Alcohol use/problems explained the relation between emotion dysregulation and psychological aggression perpetration. In addition, emotion dysregulation related to psychological aggression which explained the relation between alcohol use/problems and physical assault perpetration. CONCLUSIONS: These findings underline the importance of assessing and addressing emotion dysregulation and alcohol use/problems as risk factors for IPV in existing BIP as well as within theoretical models.